The expression of autophagy-associated protein LC3, metastasis, and chemotherapy response in colorectal cancer patients receiving uracil-based chemotherapy: An observational study - Riskie Aditya Putra, Mochammad; Rudiman, Reno; Lukman, Kiki; Am Am Setya Sulthana, Bambang; Purnama, Andriana; Ruchimat, Tommy; Wijaya, Alma; Nugraha, Prapanca; Rahmawan, Andhika (Trends in Immunotherapy, 2024)
Background: LC3 serves as a marker for assessing autophagy activity in cancer cells, which is a potential focus for therapeutic interventions. It holds the potential to serve as a predictive indicator of resistance to chemotherapy in colorectal cancer. Thus, this study is aimed at finding the association between LC3 expression, metastasis, and chemotherapy response in colorectal patients. Methods: This study was an observational study evaluating the stage and chemotherapy response of a colorectal cancer patient in a tertiary hospital in West Java, Indonesia. The research participants included in this study were 83 subjects. The examination of LC3 was performed with immunohistochemistry. The response evaluation criteria in solid tumors (RECIST) were used for the evaluation of the chemotherapy response. Results: A positive LC3 expression was shown in 58 (69.9%) patients. In positive LC3 expression, 20 subjects (27.4%) showed progressive response, 16 subjects (21.9%) showed stable response, 12 subjects (16.4%) showed partial response, and 1 subject (1.4%) showed complete response. Meanwhile, in negative LC3 expression, 12 subjects (16.4%) showed progressive response, 8 subjects (11%) showed stable response, 3 subjects (4.1%) showed partial response, and 1 subject (1.4%) showed complete response. The LC3 expression showed no significant relationship with age, sex, subtype, grade, tumor location, stage, or chemotherapy response (p > 0.05). Conclusion: The expression of LC3 showed no significant relationship with metastasis or chemotherapy response.